Delineation of local labor markets in Greece on the basis of travel-to-work flows - Dimitris Kallioras; Yorgos Kandylis; Nikos Kromydakis; Panagiotis Pantazis (European Regional Science Association (ERSA), 2011)
Labor does not move only between firms and occupations; labor moves also between geographic areas. The territorial dimension of labor markets, however, has been rather loosely conceptualized, suggesting a unity absent in practice, probably because spatial theories have been developed, to a great extent, separately from the economic ones. The recognition of the "multiplicity of sub-markets" in the real world - noticeable is the term "balkanization" - necessitates the definition of local labor market areas (LLMAs) since the geographical dimension of both production process and labor force breeds territorial partitions in the labor market, setting obstacles to - and creating opportunities for - the mobility of (potential) workers. The aim of the paper is the definition of LLMAs in Greece on the basis of travel-to-work flows (i.e. incoming and outgoing), towards the formation of better-targeted policy interventions. The definition of LLMAs is bound to establish a unit of locality which commands general acceptance as a reference for addressing issues of planning and development as well as issues of labor market, in a manner which is not possible through the conventional, administrative and/or statistical, territorial partitions. The identification of the functional linkages, under the prism of territorial structure and hierarchy, which exist within and between LLMAs is going to detect relations of interaction, overlapping and interdependence - and also discontinuities - in the Greek territory. The analysis is going to utilize the disaggregated travel-to-work data, among the 1,034 municipalities and communities, solicited in the 2001 Population Census and included in the "Panorama of Census Data 1991-2001". The aforementioned data are referred to permanent population and include both daily and seasonal travel-to-work flows.
Keywords: 330